La mesure de l'analphabétisme en question. Le cas de l'Afrique subsaharienne - Alain Mingat; Francis Ndem; Adeline Seurat (Les éditions de la Maison des sciences de l'Homme, 2013)
Sub-Saharan African countries are characterised by a high proportion of illiterate adults and this is not conducive to both economic growth and poverty reduction. Based on household surveys in which literacy is assessed on the capability of the individual to read simple sentences on a reading card, the proportion of illiterate 15-49 adults is estimated at 49.5 per cent for the Region. This estimate is about 12 points higher than that made by UIS using a more conventional approach. This difference raises questions about the definition of illiteracy. Beyond, the point is made that if the proportion of adults that are illiterate has diminished over the last two decades, their absolute number keeps rising. The increase in the size of the cohorts is indeed a basic reason to account for this twofold result ; however, this does not make the story more satisfactory in view of social progress. Besides, estimates made from a large number of household surveys underscore that the incidence of illiteracy varies widely across the countries of the region, but also within them according to individual characteristics, and in particular to the length of the studies validated during youth.